2014
DOI: 10.5539/elt.v8n1p1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Instructor Personality on Student Evaluation of Teaching: A Comparison between English Majors and Non-English Majors

Abstract: 160 non-English major students studying at a four-year university and 193 English major students studying at a career college of foreign language in Japan completed a questionnaire regarding instruction and instructor personality. The purpose of the current study was to examine whether the students' instructional and personality ratings predicted their general evaluation of course. This study also investigated whether the relations between instructional and personality ratings and the general course evaluation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
2
1
Order By: Relevance
“…With reference to Murray et al’s (1990) 29 types of teacher personality, the lecturer was perceived by the students as a meek (mild-mannered), sociable (friendly, outgoing, enjoys being with people), supporting (helpful and gives sympathy and comfort), and objective (fair and bias-free) person. Although a previous study has reported that teacher personality did not influence English majors’ evaluation of the effectiveness of their courses (Mori and Tanabe, 2015), the current research found that international English majors in the focal EMI course considered the lecturer’s personality as crucial to the effectiveness of the class. As far as these students were concerned, the lecturer’s personality determined the type of teacher-student relationship and consequently affected teaching effectiveness.…”
Section: Findings and Discussioncontrasting
confidence: 83%
“…With reference to Murray et al’s (1990) 29 types of teacher personality, the lecturer was perceived by the students as a meek (mild-mannered), sociable (friendly, outgoing, enjoys being with people), supporting (helpful and gives sympathy and comfort), and objective (fair and bias-free) person. Although a previous study has reported that teacher personality did not influence English majors’ evaluation of the effectiveness of their courses (Mori and Tanabe, 2015), the current research found that international English majors in the focal EMI course considered the lecturer’s personality as crucial to the effectiveness of the class. As far as these students were concerned, the lecturer’s personality determined the type of teacher-student relationship and consequently affected teaching effectiveness.…”
Section: Findings and Discussioncontrasting
confidence: 83%
“…There are 14 works that analyze associated factors with some form of impact on the results of the teacher evaluations made by the students; to mention a few, among these is the point at the school cycle in which the evaluation is carried out [43], the size of the groups [52], the duration of the evaluation [44], the characteristics of the students who evaluate [18], the results in learning [19,22,106] or the teacher's characteristics [2,27,32].…”
Section: Relationship Of Results and Associated Factorsmentioning
confidence: 99%
“…The practice-communication-autonomy theoretical model points out the direction for students to conduct immersive learning, and it also indicates the possible ways for students to implement the activities of immersive classroom English teaching [29,30]. Teachers let students exert their abilities in the immersive English teaching environment, and develop and enhance their actual language application abilities through set scenarios, collaborations, and conversations, etc.…”
Section: Fig 3 Deficiencies In Current Teaching Evaluationmentioning
confidence: 99%